SUGGESTION FOR AN OPTIMAL MODEL FOR E.coli, S. aureus AND C. albicans PRESERVATION AT A STORAGE TEMPERATURE IN THE RANGE OF 4°C TO -20°C - Neli Ermenlieva; Emilia Georgieva; Gabriela Tsankova; Tatina Todorova; Silvia Mihaylova (Peytchinski Publishing, 2021)
The low temperature in the storage processes can vary in the range of +4°C to -80°C and even lower, using liquid nitrogen. Depending on this, the time for which we expect the microbial culture to remain viable also changes. Agar slant culture, covered with oil, stab culture, saline suspension, glycerol and DMSO preservation, drying on silica gel, drying on soil, sterile water, lyophilization, cryopreservation, etc. are methods employed for the preservation of microorganisms. However, the choice of method to be used depends on the type of microorganism, the purpose of storage, and duration of preservation. The aim of the study is to compare storage techniques using semisolid agar and cultivation at 4°C and using BHI broth with glycerol and cultivation at -20°C. These are two commonly used and accessible methods for bacteria and yeast preservation. After performing the storage procedure for a total of 18 strains of S. aureus, E. coli and C. albicans, we re-cultivated them after two and six months of preservation. From the obtained results, we can conclude that the storage of bacteria at 4°C on semisolid agar for up to 8 weeks is successful, in C. albicans, one of the tested six strains did not survive. After 6 months, another strain of the yeasts did not show growth, as well as one of the sixth E. coli strains. Storing microbes at -20°C with a cryoprotectant has proven to be a more successful method. This was an expected result, and other authors commented that lower storage temperatures provide longer life for microorganisms.